IMPLEMENTASI DAN PROBLEMATIKA KURIKULUM MERDEKA DI SDIT RAUDHATURRAHMAH - Yuwono, Tia Dita Putri Latifa; Shaleh, Shaleh; Wijayanto, Adi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Implementation of the independent curriculum has supporting and inhibiting factors. The method used in this research is qualitative with a case study approach on the research focus at the Raudhoturrahmah Integrated Islamic Elementary School. The collected data was analyzed using the Miles, Huberman, and Saldana analysis technique. The results of this research reveal that the inhibiting factors are teachers who do not fully understand their role in the independent curriculum, heavier learning loads on student assignments, and the existence of new terms in implementing the independent curriculum. The supporting factors are monthly workshops for principals and supervisors coached by expert trainers, strengthening learning committee teachers, mentoring by expert trainers online, carrying out coaching activities for principals every month, filling out surveys to find out various obstacles in implementing the independent curriculum. This school uses an independent curriculum with independent study options in grades II, III, V, VI and the independent option changes in grades I and IV. This school has implemented an independent curriculum which begins with carrying out diagnostic assessments, adjusting lesson hours, creating projects as an implementation of the Pancasila Student Profile Strengthening Project (P5), carrying out learning that is adapted to student characteristics both outside and inside the classroom.